Multimodal Texts Implementation in Indonesian Primary and Secondary EFL Classrooms: Prospects and Challenges - Kusumaningrum, Shirly Rizki; Dewi, Radeni Sukma Indra; Mardhatillah, Mardhatillah; Pristiani, Riska; Rizal, Muhammad Syahrul; Mustakim, Sita Salina (FKIP Universitas Lampung, 2024)
Multimodal Texts Implementation in Indonesian Primary and Secondary EFL Classrooms: Prospects and Challenges. This study investigates the prospects and challenges of implementing multimodal texts in Indonesian primary and secondary EFL classrooms. Using a qualitative survey approach, data were collected from 33 English teachers in Malang City via an online questionnaire. Findings revealed that 31 teachers had integrated multimodal texts, such as videos, diagrams, audio, music, picture books, and e-learning tools, into their instruction. Teachers reported benefits, including increased student engagement and a more enjoyable learning experience. However, challenges arose, including students' struggles with multimodal learning, limited internet access, resource constraints, and a need for more teacher training. This study suggests a need for further research to design effective instructional strategies for integrating multimodal texts in EFL, especially for young learners in primary and junior high school in Indonesia. Keywords: multimodal text, primary, secondary, EFL, Indonesia.DOI: http://dx.doi.org/10.23960/jpp.v14.i3.2024102